2005
DOI: 10.1148/radiol.2361040799
|View full text |Cite
|
Sign up to set email alerts
|

Role of US in Detection of Crohn Disease: Meta-Analysis

Abstract: US examination seems appropriate for confirming or excluding Crohn disease as a diagnosis in a clinical context characterized by a pretest probability of Crohn disease that ranges from 12% to about 60%. In particular, for Crohn disease limited to the ileum, US may represent a valid alternative to the small-bowel series, while for colonic involvement US may be useful in ruling out the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
128
1
13

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(145 citation statements)
references
References 44 publications
3
128
1
13
Order By: Relevance
“…In addition, lymphoid hyperplasia is often present in the submucosa. In the small intestine, a wall thickness above 3 mm and in the colon from 2 to 3.5 mm in the proximal and distal end, respectively, are considered as pathologic [3].…”
Section: Some Pathological Conditionsmentioning
confidence: 99%
“…In addition, lymphoid hyperplasia is often present in the submucosa. In the small intestine, a wall thickness above 3 mm and in the colon from 2 to 3.5 mm in the proximal and distal end, respectively, are considered as pathologic [3].…”
Section: Some Pathological Conditionsmentioning
confidence: 99%
“…The accuracy of the examination was characterized by variability between facilities and between operators, with sensitivity values ranging from 75 to 94 % and specificities of 67-100 % [45]. Similar sensitivity (85 %) emerged from a more recent systematic review by Panes et al [46].…”
Section: Ultrasoundmentioning
confidence: 81%
“…The objective of the preoperative workup should be to provide the most precise information possible on the number, extension, and characteristics of the lesions, including the presence and predominant nature (fibrotic or inflammatory) of strictures as well as the extramural extension of the inflammatory changes. Ultrasound is limited by its operator-dependency, but it is also widely available, and in addition to characterizing strictures (with or without the aid of acoustic contrast media proposed by some), it can also reveal extramural complications of Crohn's disease, although its accuracy in this setting is inferior to that of CT [42,45,90,91].…”
Section: Jejunoileal and Ileocolic Crohn's Diseasementioning
confidence: 99%
“…Fraquelli et al [22] compared different bowel wall thickness cutoff values in a meta-analysis. A sensitivity and specificity of 88 and 93 % respectively, were observed when a bowel wall thickness greater than 3 mm was used, and sensitivity and specificity of 75 and 97 % respectively were obtained when a threshold greater than 4 mm was used.…”
Section: Ultrasonographic Features Of the Intestinal Wall In Crohn's mentioning
confidence: 99%
“…A sensitivity and specificity of 88 and 93 % respectively, were observed when a bowel wall thickness greater than 3 mm was used, and sensitivity and specificity of 75 and 97 % respectively were obtained when a threshold greater than 4 mm was used. Thus, a cutoff of 4 mm can be considered a sensible and specific limit for primary diagnosis, while a threshold greater than 3 mm can be considered a sign of active disease during follow-up [22]. Several studies showed a relation among bowel wall thickness, clinical disease activity and endoscopic findings, using the Crohn's Disease Activity Index (CDAI) at initial diagnosis and during the clinical course of CD [23,24].…”
Section: Ultrasonographic Features Of the Intestinal Wall In Crohn's mentioning
confidence: 99%